2019
DOI: 10.3390/ijerph17010245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Work Environment on Presenteeism among Aging American Workers: The Moderated Mediating Effect of Sense of Control

Abstract: With the rapid increase of aging workforces, companies worldwide are concerned with improving the health and working status of older workers. Sense of control is an important psychological variable in sociology but has attracted less attention in studies of occupational health and management. This study examined the association of sense of control with presenteeism among aging workers in the United States. Data from the Health and Retirement Survey were analyzed, specifically, 2308 observations in 2012. Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…In order to determine whether cynical hostility has an indirect effect on the relationship between work environment and recessive presenteeism in this study, we used maximum likelihood estimation [42,43] to test the mediating effect in our initial model. The local fit of the model was assessed on the basis of the following criteria: factor reliability values of 0.6 or more, indicator reliability values of 0.3 or more for each indicator of an underlying latent variable, p < 0.05 for all factor loadings, a root mean square error (RMSEA) less than 0.08, the goodness of fit, norm fitting, comparative fitting index (CFI), and tucker Lewis index (TFI) of 0.90 or higher [44]. These indicators were used to test the fitting degree of the model in previous studies [45].…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine whether cynical hostility has an indirect effect on the relationship between work environment and recessive presenteeism in this study, we used maximum likelihood estimation [42,43] to test the mediating effect in our initial model. The local fit of the model was assessed on the basis of the following criteria: factor reliability values of 0.6 or more, indicator reliability values of 0.3 or more for each indicator of an underlying latent variable, p < 0.05 for all factor loadings, a root mean square error (RMSEA) less than 0.08, the goodness of fit, norm fitting, comparative fitting index (CFI), and tucker Lewis index (TFI) of 0.90 or higher [44]. These indicators were used to test the fitting degree of the model in previous studies [45].…”
Section: Discussionmentioning
confidence: 99%
“…Sense of control and positive and negative affect were also studied by the same research groups, using data from the United States Health and Retirement Survey. Yang et al (2019) found that sense of control (comprising personal mastery and perceived constraints) mediated the relationship between psychological work environment and presenteeism [26], and Deng et al (2020) found that positive and negative affect had mediating effects on the association between discrimination and presenteeism [17].…”
Section: Studies On Mediators and Pathways Of Association Between Strmentioning
confidence: 99%
“…Individuals with acute stress disorder who have a strong sense of control are more likely to take a positive attitude to problem solving (Chen et al, 2021 ) and thus obtain a sense of value and accomplishment, which reduces job burnout. In contrast, individuals with acute stress disorder who have a weak sense of control may feel unable to change the situation through their own abilities (Pagnini et al, 2016 ) and lose confidence in work (Yang et al, 2020 ). Such individuals feel incompetent and tend to give up (Patel et al, 2018 ), which increases the likelihood of job burnout.…”
Section: Introductionmentioning
confidence: 99%